Influenza D virus exposure among US cattle workers: A call for surveillance. (12th November 2022) - Leibler, Jessica H.; Abdelgadir, Anfal; Seidel, James; White, Roberta F.; Johnson, W. Evan; Reynolds, Stephen J.; Gray, Gregory C.; Schaeffer, Joshua W.
Abstract: Although cattle are a reservoir for influenza D virus (IDV), little is known about human exposure to IDV. We assessed IDV exposure and associated health effects among United States dairy workers, a population at heightened risk of cattle zoonoses. In prospective, cross‐shift sampling of 31 workers employed at five large‐herd dairy operations in two states, we found evidence of IDV in the nasal washes of 67% of participants at least once during the 5‐day study period. IDV exposure was not associated with respiratory symptoms in these workers. These findings suggest that IDV is present in dairy cattle environments and can result in worker exposure.